Effects of lipopolysaccharide-induced inflammation on initial lung fibrosis during open-lung mechanical ventilation in rats - Krebs, Jörg; Kolz, Alexander; Tsagogiorgas, Charalambos; Lücke, Thomas (Respiratory physiology & neurobiology, 2015)
This study aimed to assess the impact of pulmonary inflammation on early fibrotic response in rats challenged with increasing doses of lipopolysaccharide (LPS). Twenty-four rats were randomized and infused with three different increasing doses of continuous LPS infusion (n=8/group) while being ventilated with low tidal volumes and open-lung positive end-expiratory pressure. Another eight animals served as uninjured control group. Hemodynamics, gas exchange, respiratory system mechanics, lung histology, α-smooth muscle actin, plasma cytokines, and mRNA expression of cytokines and type I and III procollagen in lung tissue were assessed. We found impaired hemodynamics and gas exchange as well as higher histological lung injury scores and α-smooth muscle actin expressions in the medium LPS dose compared to control and the lower LPS dose. The highest LPS dose did not cause further aggravation of these findings. In all LPS groups type I and III procollagen decreased compared to controls and there was a negative correlation between type III procollagen-RNA expression and proinflammatory mediators.
Gesehen am 29.01.2018